(untitled) (Journal of Economic Research & Business Administration, 2015)
This article examines the interaction between the state and private enterprise in the framework of national programmes, characterizing the development of forms of public-private partnership. Development of public- private partnership in Kazakhstan acquires its significance as one of the main conditions for successful economic development of our country. Interaction between public authorities and businesses, during the process of its institutionalization has nature of partnership between government and private entrepreneurs, received the name of public-private partnership , seen as a necessary condition for the development of an efficient market economy. For solving a wide range of economic problems this partnership is understood as a form of interaction between the public and the business sector on the terms of optimal risk, responsibilities and mutual benefits sharing, with governmental control.